Students' Conceptual Understanding of the DSI Model within the TaRL Approach - Ramlawati Ramlawati; Nur Indah Sari; Sitti Rahma Yunus; Nur Faisah; Zulqifli Alqadri (Jurnal Inovasi Pendidikan IPA, 2026)
The Merdeka curriculum uses differentiation in content, process, and product, with DSI process differentiation through tiered activities and varied guidance to accommodate diverse student learning styles. The research aimed to determine the level of concept understanding among students at the inquiry level, both before and after being taught using the DSI learning model based on the TaRL approach in class VIII. The subjects were 34 students from a junior high school in Makassar. This research was a pre-experimental with a one-group pretest-posttest design, involving an experimental group and a control group. Data collection used initial ability and concept understanding tests on light and optical devices through pre-tests and post-tests. Research findings showed that the student significantly improved their conceptual understanding, with average scores increasing from 6.31 on the pre-test to 16.12 on the post-test. Then, the DSI Model within the TaRL approach was effective in strengthening the students’ conceptual understanding of science subjects.